Digital Resilience in War-Affected Contexts: An MIS Framework for Restoring ICT Learning and Freelancing Capacity - Awad, Mohammed (Journal of Applied Science, Engineering, Technology, and Education, 2026)
ICT learning systems in war-affected regions face continuous disruption caused by damaged infrastructure, unstable connectivity, mobility restrictions, and psychological stress. These conditions interrupt digital-skills development and limit access to online freelancing opportunities. This paper proposes a Digital Resilience MIS Framework designed to restore and sustain ICT learning during active conflict. The framework is developed from two ICT training programs implemented in Gaza during the 2025 war, both of which operated throughout severe instability. Analysis of program documentation shows that learning continuity depended on five interconnected pillars: resilient infrastructure; adaptable instructional workflows; structured monitoring and information flow; human-centered psychosocial support; and coordinated organizational decision-making. When combined, these elements enabled the programs to maintain attendance, progress through technical content, and complete practical projects despite external disruptions. The framework offers a practical model for institutions seeking to preserve digital learning and freelance-readiness in fragile settings and contributes to MIS scholarship by demonstrating how resilience principles can be operationalized in active conflict environments.